PHP programming with MySQL - Gosselin, Don (Course Technology, Cengage Learning, 2011)
This book covers the basics of PHP and MySQL along with introductions to advanced topics including object-oriented programming and how to build Web sites that incorporate authentication and security. After you complete this course, you will be able to use PHP and MySQL to build professional quality, database-driven Web sites.